Development of Funginite on Muaraenim and Lower Members of Telisa Formations at Central Sumatra Basin - Indonesia - Budi Prayitno; Nining Sudini Ningrum (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
Petrography analysis of coal is the study organic and inorganic components of coal bearing formations. This research conducted observation method under microscopic of thin incision to identify organic maseral group. The organic composition of coal from Muaraenim Formation is known to average for vitrinite maseral group 79.30%, inertinite 10%, liptinite 3.4%, and non-organic 7.3%. While the composition of coal from the Bottom Members of Telisa Formation for the average of vitrinite maseral group 66.4%, mineral matter 30.32%, inertinite 3.26%. The liptinite maseral group is not present as a coal component in the study area. The funginite development of the Muaraenim Formation is quite abundant 2.8% indicating peat swamp ecosystem in wet-dry conditions in ph 3 -5. In contrast, the development of funginite Lower Members of Telisa Formation is known to be absent which is replaced by the presence of frambiodal pyrite and indicates peat ecosystem in wet conditions at ph 6 - 7.